Penguatan Resiliensi Anak Pascabanjir melalui Program Trauma Healing di Gampong Meunasah Lhok, Kabupaten Aceh Utara - Depita Kardiati; Murniati Murniati; Arinanda Arinanda; Sarrah Kurnia Fadhillah; Almuna Ramadhani; Mira Humaira; Dian Arlianty (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Flood disasters not only cause physical damage but also have significant psychological impacts on children as one of the most vulnerable groups. Children in Gampong Meunasah Lhok, North Aceh Regency, experienced various post-disaster psychosocial problems, including anxiety, fear, social withdrawal, and decreased self-confidence. This community service program aimed to enhance children's resilience after flooding through the implementation of the Children's Adaptive Resilience Enhancement (CARE) model integrated with the Participatory Action Research (PAR) approach. The program involved children, village officials, parents, and community leaders through four sequential stages. The activities began with Connect & Comfort, which focused on building emotional connections and creating a sense of safety, followed by Expressive Arts & Assessment through expressive art therapy and psychological assessment. The next stage, Reframing & Narrative Storytelling, encouraged children to reframe their traumatic experiences through storytelling, while the final stage, Education for Disaster Preparedness, provided disaster preparedness education to strengthen children's adaptive resilience. The results demonstrated positive improvements in the children's psychosocial condition, as reflected by their increased ability to express emotions, restored self-confidence, greater participation in group activities, and improved knowledge of disaster preparedness.